TINDAK TUTUR KOMISIF DALAM DEBAT PUBLIK CALON WALIKOTA DAN WAKIL WALIKOTA SINGKAWANG TAHUN 2017 - Lidiawati, Lidiawati; Saman, Sisilya; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSpeech acts have a function as a communication tool to convey the message or speaker's intent to the speech partner. During the debate, the debate participants argued that they expressed their vision and mission to convince the public to choose one of the candidates for Singkawang mayor and deputy mayor in 2017 and an implementation plan in Indonesian language lessons at school. The method used in this research is descriptive method. The data in the study were transcribed speech sentences that contained speech acts of promises and offer commissives contained in the public debate of the mayor and deputy mayor of Singkawang in 2017. The techniques used were documentary techniques. The data collection tools used in the study is the researcher herself as instruments. Based on the results of the analysis of the commissive speech act data in the debates of the 2017 singkawang mayor and deputy mayor candidates, the researcher found out 33 data on the commissive speech acts, which are consist of 22 commissive promises of speech acts and 11 offer speech acts. This research was implemented in the high school grade X class 2 semester at basic competencies (KD) 3.12 connects problems/issues of perspectives and arguments of several parties and conclusions from the debate to find the essence of the debate. Keywords: speech acts, commissive speech acts, mayor debates.